Meta Analisis: Pendekatan Saintifik Terhadap Hasil Belajar Siswa - Putri, Kharisma Eka (JURNAL PENDIDIKAN DASAR NUSANTARA, 2020)
The purpose of this study is to analyze the effect of the scientific approach on the student learning result of Class Subjects, Themes, and Learning Media in elementary schools. In this study using a meta-analysis research method with 10 articles samples from national journals and the instrument is a coding category. The meta-analysis research shows that on the subject class, the scientific approach has a high effect on the student learning result on low grade subjects. For the subject of learning themes, the scientific approach has a high effect on the student learning result in non-theme learning. While from the subject of instructional media, the scientific approach has a high effect on the student learning result in the “papan berpaku” media.